Institutional ethics and stress in the working place - Perales Cabrera, Alberto (2008)
After reviewing key concepts on the issue, the author defines what institutional ethics is and outlines its functions within the organizational culture and dynamics of a health care institution. He points out that solidarity and justice constitute their fundamental basis intertwined in a good communication net. Finally, he sets forth that whenever institutional ethics is affected and stress in the working place occurs, the alteration of the three aforementioned variables leads to the most evident manifestations of this condition.